PELAYANAN PUBLIK DI KANTOR SAMSAT (Studi Tentang Persepsi Wajib Pajak Terhadap Pelayanan Pajak Kendaraan Bermotor dan Bea Balik Nama Kendaraan Bermotor Bulan April 2013 di Kantor Sistem Administrasi Manunggal Satu Atap (SAMSAT/UP3AD) Kabupaten Grobogan) - Anindya Liani; Budi Setiyono; Turtiantoro . (Journal of Politic and Government Studies, 2013)
This research will discuss about the existing public service in government agencies, particularly the SAMSAT Office of Grobogan. In this context see if the service provided by SAMSAT Office of Grobogan Regency has been of good quality or not. Quality public services that will be studied based on the principle of public service by Peraturan Menpan No. 36 Tahun 2012 and refers to the components the standards of public service in accordance with UU No. 25 Tahun 2009 tentang Pelayanan Publik. The end result of this research is the perception of the community as a respondent to the study of public service quality in SAMSAT Office of Grobogan Regency, which then can provide feedback suggestions to the promotion of quality public services in SAMSAT Office of Grobogan Regency particularly in the service of payment the PKB and BBNKB. Based on research results this, public service which exist in the SAMSAT Office of Grobogan Regency already good, indicated by the high level of public satisfaction with services and payment agreements PKB and BBNKB by existing services officer. The services provided are in accordance with the standards established service operations and service complaints are rarely found by the taxpayer, if there is a direct complaint could be resolved in accordance with the duties and functions of each official. Keywords: Public Service, Quality Service, Taxpayer Perception